Casting aluminum alloys - Zolotorevsky, Vadim Semenovich (Elsevier, 2007)
This monograph provides a broad overview of the principles of design of advanced casting aluminium alloys. These materials continue to play a very important role in a number of fields, e.g. the automotive industry, machine engineering, marine construction, etc. The authors show that the development of novel casting aluminium alloys is impossible without understanding the corresponding phase diagrams, both equilibrium and non-equilibrium, and deep relationships existing among alloy thermodynamics, phase equilibria, and alloy microstructure. An important feature is the systematic review of such.